3x-3=-4x-6

Simple and best practice solution for 3x-3=-4x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-3=-4x-6 equation:


Simplifying
3x + -3 = -4x + -6

Reorder the terms:
-3 + 3x = -4x + -6

Reorder the terms:
-3 + 3x = -6 + -4x

Solving
-3 + 3x = -6 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-3 + 3x + 4x = -6 + -4x + 4x

Combine like terms: 3x + 4x = 7x
-3 + 7x = -6 + -4x + 4x

Combine like terms: -4x + 4x = 0
-3 + 7x = -6 + 0
-3 + 7x = -6

Add '3' to each side of the equation.
-3 + 3 + 7x = -6 + 3

Combine like terms: -3 + 3 = 0
0 + 7x = -6 + 3
7x = -6 + 3

Combine like terms: -6 + 3 = -3
7x = -3

Divide each side by '7'.
x = -0.4285714286

Simplifying
x = -0.4285714286

See similar equations:

| -20m=-80 | | 27+x+35+23=180 | | X^2+6x+10=-2x-6 | | C^3-10=17 | | 60+65+50+35+x=180 | | (x+3)(3x-2)=5(3x-2) | | 5a+36=61 | | 86+84+36+x=180 | | 1-x=x+x | | 3(y-2)=y-8 | | 40=3w+5w | | 4x^2-3x+285=0 | | 42=8w-2w | | 36x^3+6x^2-6x=0 | | Tan(50)=x/121 | | 28y+4=3y^2 | | x+5=222222222222 | | 28-2m=4 | | 7x^6+x-1=0 | | 5(g-3)+2(y-2)=4 | | 1.47+1.9m=-2.1(m+2.5) | | 2.8(2.9n-1.8)=9.576+2.9n | | -6(-7x-8)+6(x-8)=-8x+7x | | 5+2n=-(-3-2n) | | 3x^2+6=4 | | 5m+38=7(-2m+2)-3m | | 2m^2-4m=48 | | -2(1+6n)=-2-8n | | 37x36/6 | | x+4-6=4-x | | 3a^2+22a=-7 | | 5x+3y-13=0 |

Equations solver categories